European guidelines for the diagnosis and treatment of pancreatic exocrine insufficiency UEG, EPC, EDS, ESPEN, ESPGHAN, ESDO, and ESPCG evidence-based recommendations - Dominguez-Muñoz J Enrique (UNITED EUROPEAN GASTROENTEROLOGY JOURNAL, 2025)
Pancreatic exocrine insufficiency (PEI) is defined as a reduction in pancreatic exocrine secretion below the level that allows the normal digestion of nutrients. Pancreatic disease and surgery are the main causes of PEI. However, other conditions and upper gastrointestinal surgery can also affect the digestive function of the pancreas. PEI can cause symptoms of nutritional malabsorption and deficiencies, which affect the quality of life and increase morbidity and mortality. These guidelines were developed following the United European Gastroenterology framework for the development of high-quality clinical guidelines. After a systematic literature review, the evidence was evaluated according to the Oxford Center for Evidence-Based Medicine and the Grading of Recommendations Assessment, Development, and Evaluation methodology, as appropriate. Statements and comments were developed by the working groups and voted on using the Delphi method. The diagnosis of PEI should be based on a global assessment of symptoms, nutritional status, and a pancreatic secretion test. Pancreatic enzyme replacement therapy (PERT), together with dietary advice and support, are the cornerstones of PEI therapy. PERT is indicated in patients with PEI that is secondary to pancreatic disease, pancreatic surgery, or other metabolic or gastroenterological conditions. Specific recommendations concerning the management of PEI under various clinical conditions are provided based on evidence and expert opinions. This evidence-based guideline summarizes the prevalence, clinical impact, and general diagnostic and therapeutic approaches for PEI, as well as the specifics of PEI in different clinical conditions. Finally, the unmet needs for future research are discussed.